Simulation and Analyses of Turbulent Flow in Different Phases of Stenosed Renal Artery - Zia Zahra; Ami Faisal; Hussain Mudasir; ur Rehman Zia; Arzak Semab Shahazadi (MATEC Web of Conferences, 2023)
This study concerns the two-dimensional structure computational results of renal artery stenosis. In this paper, the turbulent flow of the stenosed vessel is stimulated and correlates the different stages of stenosis with each other. As we know that the blood flow in most blood vessels is laminar, but in case of stenosed vessel, the blood flow becomes turbulent; this is due to the blockage that blood does not flow linearly and produces chaos. Several liquid parameters are analyzed, such as pressure, velocity, turbulence kinetic energy, density, and shear rate. The inlet and outlet flow are especially concerning. For this purpose, we explored the stenosed behavior by the software COMSOL Multiphysics which provided us with a complete examination of the Computational fluid dynamics. With an increase in renal artery stenosis, there is a decrease in the blood flow which will automatically affect the pressure of the blood and can cause serious kidney diseases and, in some cases, permanent damage to the kidney sometimes. This paper highlights the early stages of renal artery stenosis, which are likely to be cured. Also, it shows the behavior of the severe late stages, which we consider nearly impossible to cure. The result explains that how different parameters vary according to stated cases.